2020
DOI: 10.1002/mame.202000633
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Speciation, and Biological Studies on Metal Chelates of Carbohydrates with Molecular Docking Investigation

Abstract: The role of starch aerogel (St‐AG) and carboxymethyl cellulose (CMC) as biolgical active compounds, when they subjected for complexation with metal ions, is assessed in this work. The complexation is carried out with palladium(II) and copper(II) ions, in solid state. Different tools of analysis are carried out to characterize and elucidate the structures of these complexes, namely: elemental analysis, IR, thermal analysis, magnetic measurement and molar conductance techniques. All synthesized complexes are for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Platinum (Pt) drugs are the most successful class of inorganic medicinal compounds used to treat cancer [47 and 48]. Numerous metals specially Pd (II) and Cu (II) complexes have promising activity against tumor cell lines have been synthesized and published [49][50][51][52][53][54]. In addition to vanadium which has a potential role in tumor growth inhibition and in prophylaxis against different experimental cancer models like; liver cancer, colon cancer, breast cancer and others and in various types of malignant cell lines.…”
Section: Cytotoxicity and Molecular Docking Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum (Pt) drugs are the most successful class of inorganic medicinal compounds used to treat cancer [47 and 48]. Numerous metals specially Pd (II) and Cu (II) complexes have promising activity against tumor cell lines have been synthesized and published [49][50][51][52][53][54]. In addition to vanadium which has a potential role in tumor growth inhibition and in prophylaxis against different experimental cancer models like; liver cancer, colon cancer, breast cancer and others and in various types of malignant cell lines.…”
Section: Cytotoxicity and Molecular Docking Investigationmentioning
confidence: 99%
“…[54,55] Numerous metal complexes have potent activity against tumor cell lines specially Pd (II) and Cu (II) complexes. [42,[56][57][58][59][60] Vanadium has a potential role in the growth inhibition of various tumor types such as breast, colon, liver, and cancer. The cytotoxicity against MCF-7 cancer cell line was carried out by using different concentrations (1-50 μg/ml) of the investigated Schiff base NBM and its metal chelates.…”
Section: Cytotoxicity and Molecular Docking Investigationmentioning
confidence: 99%
“…Surprisingly, aerogel-based SIMs or SMMs have not yet been reported, and even aerogels that are modified with magnetic metal complexes have very rarely been mentioned. Khalf-Alla et al immobilized square planar Pd(II) and octahedral Cu(II) complexes in starch and carboxymethyl cellulose aerogels, to produce antimicrobial and anti-cancer materials [ 54 ]. He et al reported iron- and nitrogen-codoped carbon nanocomposites with single-copper sites to reduce the magnetic moment of iron centers and to enhance the electrocatalytic performance of the material [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functionalized paper, carbon nanostructures materials, semiconductor, water purification adsorbent, liquid crystal materials and the formaldehyde-free adhesive are literature applications for the cellulose-based products (Hosny et al , 1997; Vimala et al , 2009; Thakur et al , 2013; El-Saied et al , 2016; Canejo et al , 2017; Lotfy et al , 2018; Ravichandran et al , 2018; Basta et al , 2011, 2013, 2014, 2019; Ates et al , 2020). Additionally, there are medical and agriculture applications for the cellulose and its derivatives which are produced in form of hydrogel formulation (Lotfy and Basta, 2020; Lotfy et al , 2020; Hanna et al , 2020; Khalf-Alla et al , 2020; Basta et al , 2020, 2021a, 2021b, 2021c, 2021d, 2021e; Basta and Lotfy, 2021).…”
Section: Introductionmentioning
confidence: 99%